Formação continuada de formadores técnicos de Secretaria de Educação - Ferreira, Ana Paula Alves Pereira (2018)
This research aims to invetigate the processes of continuing education of teachers educators and PC of the pedagogical wokshop promoted by the Francisco Morato Municipal Education System, considering that the educators, as well as other persons, are uncompleted individuals also in their professional practices and, while developing teachers education actions, they too need to be educated. For that, the research is guided by questions such as: Wich are the continuing education actions that the educators have been experienced? What has the Education Secreteriat done on behalf of this formation? Which aspects may complicate the educators? The Municipal Education Secretariat maintain a Pedagogical Center responsible for the teachers continuing education, which consists of Pedagogical Technical Assitants whom are teachers and coordinators educators. In order to reflect and clarify the continuing education actions to which the educators undergo and/or are submitted, this study uses the statement of six educators whom were interviewed. The study was also guided by official municipal documents, in order to search for evidences which could define the role of the teachers educator, so that they may outline their work and assure the continuing education of the Municipal Education System professionals. The concepts covered in this work are adult learning, continuing education, self-learning and professional knowledges, supported by the theoretical background of Barbier (2013), Freire (1996), Galvani (2002), Marcelo Garcia (1999), Imbernón (2010; 2012; 2015), Josso (1988; 2004), Vaillant and Marcelo Garcia (2012), Nóvoa (2009), Pineau (1988), Placco e Souza (2006) and Vaillant (2012). The data from the interviews were analyzed according to six categories: conception of training, to learn from each other, self-learning, to learn inthe professional practice, to learn from institutional propositions and the formation obstacles. The work was able to determine that the continuing education is much more realized by personal initiative of the own educator that by managment initiatives, and that their learning happens from the interaction winth the peers and trainees, during the reading and the formative activities of which they take part. The institution allow some formative specific actions to its educators which contribute with the learning, but it could do more. The work concludes, in addition, that the teacher and educator’s educator is also a professional that feels lonely performing her or his work and educating other people. There are still a long run towards an in fact teamwork